(untitled) (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The research was conducted to study the effect of a complex antimicrobial drug with an anti-inflammatory effect and an antimicrobial drug with an immunostimulating effect on the parameters of nonspecific resistance in calves. Materials and Methods: Two groups (n = 5 each) of sick calves with respiratory pathology were selected for this study. For the treatment of the first experimental group, a complex antimicrobial drug Sulfetrisan® was used. The second experimental group of the calves was intramuscularly injected with the experimental drug gentaaminoseleferon (GIA). To assess the cellular component of immunity in the blood before and after treatment, the number of white blood cells, T-lymphocytes, B-lymphocytes, phagocytic activity of leukocytes, phagocytic number, and phagocytic index (PhI) were determined. In addition, for assessing the humoral component, serum complement activity (SCA), serum lysozyme activity, serum bactericidal activity (SBA), circulating immune complexes (CIC), and total immunoglobulins (total Ig) were measured. The results were compared with the baseline parameters of healthy calves of the control group. Results: When studying the parameters of the humoral and cellular components of nonspecific resistance, it was found that in sick animals, compared with healthy ones, respiratory pathology was accompanied by an imbalance in the immune system. In the process of recovery in animals of the experimental groups under the effect of the drugs, positive changes occurred. However, many of the studied parameters did not reach the values of healthy animals. In the group of calves that received GIA, compared with the calves given Sulfetrisan®, a significant increase in PhI (p < 0.05), SBA (p < 0.006), SCA (p < 0.05), total Ig (p < 0.0005), and CIC (p < 0.05) was observed, which indicated an increase in natural resistance due to the immunostimulating action. Conclusion: The use of GIA in sick animals added to an increase in the general nonspecific cellular and humoral resistance of calves, which made it possible to increase therapeutic efficacy and shorten their recovery time. J. Adv. Vet. Anim. Res., 8(3): 355-360, September 2021 http://doi.org/10.5455/javar.2021.h522